Good Clinical Practice Training: Identifying Key Elements and Strategies for Increasing Training Efficiency. (July 2016) - Arango, Jaime; Chuck, Tina; Ellenberg, Susan S.; Foltz, Bridget; Gorman, Colleen; Hinrichs, Heidi; McHale, Susan; Merchant, Kunal; Seltzer, Jonathan; Shapley, Stephanie; Wild, Gretchen
Good Clinical Practice (GCP) is an international standard for the design, conduct, performance, monitoring, auditing, recording, analyses, and reporting of clinical trials. The goal of GCP is to ensure the protection of the rights, integrity, and confidentiality of clinical trial participants and to ensure the credibility and accuracy of data and reported results. In the United States, trial sponsors generally require investigators to complete GCP training prior to participating in each clinical trial to foster GCP and as a method to meet regulatory expectations (ie, sponsor's responsibility to select qualified investigators per 21 CFR 312.50 and 312.53(a) for drugs and biologics and 21 CFR 812.40 and 812.43(a) for medical devices). This training requirement is often extended to investigative site staff, as deemed relevant by the sponsor, institution, or investigator. Those who participate in multiple clinical trials are often required by sponsors to complete repeated GCP training, which is unnecessarily burdensome. The Clinical Trials Transformation Initiative convened a multidisciplinary project team involving partners from academia, industry, other researchers and research staff, and government to develop recommendations for streamlining current GCP training practices. Recommendations drafted by the project team, including the minimum key training elements, frequency, format, and evidence of training completion, were presented to a broad group of experts to foster discussion of the current issues and to seek consensus on proposed solutions.